2018
DOI: 10.1002/ppul.23967
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, cost effectiveness, and sustainability of a pediatric high risk asthma clinic

Abstract: A pediatric High Risk Asthma clinic model is efficacious in decreasing hospitalizations and Emergency Department visits for a difficult to treat population, and such a model can be cost-effective and sustainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with other evidence from the USA, France, Australia and the Netherlands [7][8][9][10][11][12][13] which have demonstrated that specialist assessment can lead to improved asthma control, reduced exacerbations and a lowering of mOCS dose. Our results are also in broad agreement with evidence from the UK [24,25], including within the most recent study by Gibeon et al [14] which used data collected from UK severe asthma centres between 2009 and 2010.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with other evidence from the USA, France, Australia and the Netherlands [7][8][9][10][11][12][13] which have demonstrated that specialist assessment can lead to improved asthma control, reduced exacerbations and a lowering of mOCS dose. Our results are also in broad agreement with evidence from the UK [24,25], including within the most recent study by Gibeon et al [14] which used data collected from UK severe asthma centres between 2009 and 2010.…”
Section: Discussionsupporting
confidence: 92%
“…There has been much interest investigating the benefits of specialist assessment and management since it was recommended for difficult to control asthma over thirty years ago [6]. Studies in the USA, France, Australia and the Netherlands [7][8][9][10][11][12][13] have demonstrated that specialist assessment can lead to improved asthma control, reduced exacerbations and a lowering of maintenance oral corticosteroid dose (mOCS) dose. These findings have been replicated within several UK-based studies and, most recently, Gibeon et.…”
Section: Introductionmentioning
confidence: 99%
“…Multidisciplinary asthma clinics have been shown to reduce visits to the emergency room, decrease hospitalizations, and improve asthma severity and quality of life. 8,9,11,12 We are currently working to create spaces where families and patients can meet, receive education, share their experiences, and provide peer support and empowerment. Thus far, we have had three virtual support group sessions that have been well attended.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Multidisciplinary care for complex medical issues has been well described in the pain literature 6 but has yet to be widely adopted for severe childhood asthma despite some supportive findings. [7][8][9][10][11][12] A multidisciplinary clinic provides a standardized approach for the management of children with severe asthma, as recommended by current guidelines. 1,7,13 To better understand and care for our pediatric patients with difficult-to-treat and severe asthma, we created a multidisciplinary Severe Asthma Clinic (SAC) by bringing together an Allergist and a Pediatric Pulmonologist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation